Teacher Strategies in Developing Tolerance Attitudes in Students at SMPIT Al-Anis Kartasura - Utami, Hanida Putri; Azzani, Mohammad Zakki; Maksum, Muhammad Nur Rochim (Universitas Muhammadiyah Surakarta, 2023)
This research aims to describe teachers' strategies for developing students' attitudes of tolerance at SMPIT AL-Anis Kartasura. This research is qualitative research with a descriptive qualitative research type, with a research approach in the form of phenomenology. The data in this research was obtained using data collection techniques in the form of observation, interviews, and documentation. Next, the data was analyzed using the Miles and Huberman model analytical technique through 3 stages: data reduction, data presentation, and verification or conclusion. The results of this research show that teachers have made various efforts to develop an attitude of tolerance towards students at SMPIT AL-Anis Kartasura so that regular students and students with special needs have the same opportunities and rights in obtaining education. From this research, it was concluded that the teacher's strategy in instilling an attitude of tolerance in students at the school was by preparing lesson plans, giving advice or warnings to students, being an example or role model in behavior, using group discussion methods in learning, and familiarizing all students with to mingle with each other through routine school activities without differentiating between them.